2016
DOI: 10.7205/milmed-d-15-00435
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Loads and Lifting are Risk Factors for Musculoskeletal Injuries in Deployed Female Soldiers

Abstract: The purpose of this prospective cohort study was to investigate physical, occupational, and psychosocial risk factors for musculoskeletal injuries (MSI) in deployed female soldiers. Before deployment, participants completed performance testing and surveys and after deployment an additional survey detailing occupational demands and MSI. Data analyzed found 57/160 (36%) suffered 78 MSI. In unadjusted analyses, these factors increased the relative risk (RR, 95% confidence interval) of injury: wearing an average l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 153 publications
(484 reference statements)
0
31
0
Order By: Relevance
“…The present study did not identify BMI as a predictor of attrition in female light infantry soldiers, which might be explained by the narrow distribution of BMI values in the tested population, in which 47.3% of subjects were of normal weight, and less than 10% were either underweight or obese. The lack of a relationship between BMI and attrition in military recruits has previously been reported, and US Army data showed that the BMI of a recruit was not related to the rate of attrition during basic combat training [7,8,26,37,38]. Also, a study that measured the attrition among male and female soldiers found that enlistees who exceeded normal weight and amounts of body fat, but passed an endurance step-test and push-up test, did not have a significantly increased risk of attrition when compared with recruits with normal weight and body fat measurements [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study did not identify BMI as a predictor of attrition in female light infantry soldiers, which might be explained by the narrow distribution of BMI values in the tested population, in which 47.3% of subjects were of normal weight, and less than 10% were either underweight or obese. The lack of a relationship between BMI and attrition in military recruits has previously been reported, and US Army data showed that the BMI of a recruit was not related to the rate of attrition during basic combat training [7,8,26,37,38]. Also, a study that measured the attrition among male and female soldiers found that enlistees who exceeded normal weight and amounts of body fat, but passed an endurance step-test and push-up test, did not have a significantly increased risk of attrition when compared with recruits with normal weight and body fat measurements [39].…”
Section: Discussionmentioning
confidence: 99%
“…The backpack weight was reduced due to the difference between the studied populations: male soldiers (mean height: 1.81±0.06 m; mean weight: 75.3±7.5 kg) compared with female soldiers (mean height: 1.61±0.06 m; mean weight: 61.8±10.2 kg), and was selected based on a pilot test with female soldiers, which identified the optimal weight to perform the test. A previously modified version of the Ranger Test that was also performed on female soldiers (median height: 1.60 m; median weight: 66.3 kg) used a 17 kg vest but reduced the bench height to 0.3 m [37]. However, in this previously published study, the soldiers were pre-deployment and past basic training, enabling a more strenuous test to be used [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to cumulative effect through time of service as senior military personnel has longer exposure of physical load than junior military personnel. Earlier studies have also reported effects of gender on the development of low back pain [42,43]. Bar-Dayan et al [41] (OR = 1.93, CI 1.89-1.98), Feuerstein et al [16] (OR = 6.59, CI 1.79 -24.24), Knox et al [9] (IRR = 1.45) has discovered that females has increased low back pain risk as compared to their male counterparts.…”
Section: Personal Risk Factors Of Lbp In the Militarymentioning
confidence: 94%
“…The findings of narrative review by Waqqash et al [20] revealed that army personnel have high occupational physical exposure as their job scope requires usage of heavy body armour for a prolonged duration, heavy carrying and lifting, standing and marching for a long duration, and undergoing rigorous physical and combat training. According to Roy et al [16], the relative risk rates for LBP identified among army personnel are: (1) wearing a load more than 10% BW (RR = 2.00, 1.31-4.57), (2) wearing an average load for more than 1 hour (RR = 2.44, 1.30-4.57), (3) load worn more than 15% BW (RR = 5.83, 1.51-22.50), (4) wearing a backpack (RR = 1.82, 1.23-2.80), (5) wearing body armour >1 hour (RR = 1.62, 1.002-2.62), (6) Lifting objects weighing above 22.68 kg (RR = 1.96, 1.08-3.57), (7) Lifting objects one to two times (RR = 1.73, 1.002-2.97), and (8) carrying objects more than 7.62 m (RR = 2.01, 1.19-3.42).…”
Section: Introductionmentioning
confidence: 99%